COMPULSIVE BUYING AND FINANCIAL FACTORS: EVIDENCE FROM TURKEY (Third Sector Social Economic Review, 2019)
This research examines the relationships between compulsive buying and financial factors such as: Money attitudes, credit card use and  perceived financial well-being. Findings showed that power-prestige has a negative and significant effect and anxiety, compulsive buying and credit card use have a positive and significant effect on perceived financial well-being. Power-prestige and credit card use have a positive and significant effect on compulsive buying. Retention-time has a negative and significant effect on credit card use. Different from past studies, the current study combines money attitudes, credit card use, and compulsive buying with perceived financial well-being from the point of younger Turkish consumers.
Keywords: Money Attitudes; Credit Card Use; Compulsive Buying; Perceived Financial Well-being.